Gerakan Masyarakat Desa Suralaga Bebas Stunting melalui Optimalisasi Web-Based Literacy 'Stunt Guard' - Yosi Nur Kholisho; Jamaluddin Jamaluddin; Kholida Ismatulloh; Rasyid Hardi Wirasasmita; Zamroni Uska; Baiq Desi Dwi Arianti; Mefthafayra Odilia Irham (Al-Tafani: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2026)
Stunting remains a major public health challenge in Indonesia, particularly in rural areas. This community service program aims to enhance health literacy and digital skills among residents of Suralaga Village by optimizing the “Stunt Guard” web application as an educational and monitoring tool for stunting prevention. Activities included socialization, training, and intensive mentoring for posyandu cadres and mothers of young children. Evaluation using pre-test and post-test revealed a significant increase in participants’ knowledge and preventive behaviors after the intervention. These results indicate that utilizing web-based applications is effective in strengthening community involvement in monitoring child growth and supporting participatory, sustainable stunting prevention efforts. This program is expected to serve as a replicable digital empowerment model to accelerate the reduction of stunting rates in Indonesia.